Synergistic numerical and experimental simulations to evaluate a surface probe to determine body core temperatures. (18th May 2016) - Tan, W.; Sparrow, E. M.; Gorman, J. M.; Minkowycz, W. J.
ABSTRACT: A highly accurate noninvasive means of determining body core temperature is proposed and characterized by synergistic use of numerical and experimental simulations. It was demonstrated that the new surface probe yields skin surface temperature measurements that are within a few tenths of a degree of the body core temperature. Advanced simulation techniques such as the Monte Carlo method for the determination of radiant heat losses were used to ensure high accuracy. Convective heat losses were also accounted. Full account was taken of the multilayer nature of the tissue bed beneath the skin surface, each layer with its specific thermophysical properties, blood perfusion, and metabolic heating. For the validation of the numerical simulation model, an experimental apparatus was fabricated and operated. The experimental data supported the numerical predictions. The capability of the probe to accurately follow thermal transients was the focus of a redesign, yielding small-fraction-of-a-minute following capability.